An end-to-end service provisioning scenario for the residential environment. - Duenas, Juan C.; Ruiz, Jose L.; Santillan, Manuel
The home of the future is here, or at least the hardware to support it. Home environments are currently characterized by the existence of a wide variety of connected devices. This infrastructure is useful in itself. However, we could get much more from it. We could use it to provide advanced services to the end user. This article presents the experience acquired during the design and implementation of an end-to-end service provisioning platform. We have followed a standards-driven approach to leverage existing middleware with open source assets. The selected middleware-platforms are the OSGi service platform at the residential end, J2EE technologies at the service provider end, and Web services for coarse-grained coordination and interaction between the different actors. In this way we create a suitable environment for all the stakeholders.
Keywords: J2EE technologies; Web services; coarse-grained coordination; end-to-end service provisioning scenario; middleware; open source assets; residential environment; service platform; service provider